PELAKSANAAN PUTUSAN MAHKAMAH KONSTITUSI NO. 10/PUU-XVIII/2020 ATAS MEKANISME PENGUSULAN KETUA DAN WAKIL KETUA PENGADILAN PAJAK - Tommy Valentino Sugiono; Supriyadi Supriyadi (JURNAL PAJAK INDONESIA, 2021)
As a special court within the state administrative court, The Tax Court normatively has particular characteristics. One of these characteristics is the authority of the Minister of Finance to propose the Chairman and Deputy Chairperson of the Tax Court by the provisions of Article 8 paragraph (2) of Law Number 14 of 2002 of the Tax Court. Based on the Decision of Case Number 10/PUU-XVIII/2020 on the petition for judicial review of the article, the Constitutional Court decided to grant part of the petition. Thus, the authority of the Minister of Finance is only administrative in nature. This study aims to determine the mechanism and the views of judges and academics regarding the election of the Chairman and Deputy Chairperson of the Tax Court both before and after the Constitutional Court Decision. The research was conducted with qualitative research methods using a library research approach and interviews. Based on this research, it is known that: there are differences in the mechanism for selecting the Chair and Deputy Chair of the Tax Court either before and after the decision of the Constitutional Court; there is a certainty for Tax Court judges after the Constitutional Court Decision; Tax Court judges are independent in deciding tax disputes.